Macht Arbeit Frei? : German Economic Policy and Forced Labor of Jews in the General Government, 1939-1943. - Medykowski, Witold. (Jews of Poland Series, 2018)
This is the first ever study to address Jewish forced labor in the General Government (Poland) during the Holocaust, and its consequences on the Nazi regime. A fascinating book about mutual dependence of economics and warfare during one of the most difficult periods in human history.